Comparison of children with bioinactive growth hormone, small for gestational age, and idiopathic short stature - Özdemir, Esma Kaya; Döğer, Esra; Çamurdan, M. Orhun; Bideci, Aysun (Frontiers in Endocrinology, 2025)
IntroductionShort stature has many causes, including rare disorders of GH function. Bioinactive growth hormone (GH) refers to a phenotype characterized by immunoreactive but biologically ineffective GH. Importantly, it should not be regarded as a separate treatment but rather as a definable subgroup within the broader population of children receiving recombinant human growth hormone (rhGH) therapy. The aim of this study was to compare the growth response to rhGH among children with bioinactive GH, those born small for gestational age (SGA), and those with idiopathic short stature (ISS).MethodsIn this retrospective, single-center study, we reviewed the medical records of short-statured patients with a height ≤ –2 z-score, a normal peak GH response (≥10 ng/mL) to clonidine or L-dopa stimulation tests, and a history of rhGH treatment. Patients with chronic illness, malnutrition, syndromic or endocrine disorders, diabetes, metabolic disease, anemia, or prior pubertal suppression were excluded. Eligible patients meeting the definitions of bioinactive GH, SGA, or ISS were included.Statistical AnalysisData were analyzed with IBM SPSS Statistics 22.0 using parametric and non-parametric tests with Bonferroni correction; significance was set at p < 0.05.ResultsAmong 170 patients screened, 109 fulfilled the criteria for analysis (bioinactive GH, n=8; SGA, n=27; ISS, n=74). Baseline Insulin-like Growth Factor 1 (IGF-1) and Insulin-like Growth Factor Binding Protein 3 (IGFBP-3) levels were markedly lower in the bioinactive GH group compared with SGA and ISS (p < 0.001). During rhGH therapy, patients with bioinactive GH exhibited the greatest gains in growth velocity and Δ height z-score, despite similar GH doses and a lower proportion of pubertal subjects. By final height, all patients with bioinactive GH achieved normal stature, with most surpassing target height, whereas fewer SGA and ISS patients reached their genetic potential.ConclusionChildren with bioinactive GH form a biologically distinct and highly treatment-responsive subgroup of non-GHD short stature. Our findings highlight the diagnostic value of IGF-1 generation testing in this context. Future multicenter studies with genetic and bioactivity confirmation are essential to refine diagnostic criteria and establish international guidelines.